The Influence of Learning Model Problem Based Learning in Group Investigation Against Learning Outcomes And Activeness Basic Computers and Networks - Utomo, Firmansyah Nur; Efendi, Agus; Wihidayat, Endar Supri (Journal of Informatics and Vocational Education, 2019)
This study aims to find out (1) whether there are differences in learning outcomes in the application of learning models Problem Based Learning in Group Investigation with conventional learning models; (2) Are there differences in student learning activeness in the application of learning models Problem Based Learning in Group Investigation with conventional learning models (3) Is the application of learning models Problem Based Learning in Integrated Group Investigation more effective than conventional learning. This study used the quasi-experimental design method with a pretest-posttest control group design model. The population in this study were students of X Axioo class and X RPL B of SMK Negeri 5 Surakarta. The sample used was 70 people. The sampling technique used is total sampling. Data collection techniques using pretest-posttest and observation sheet. The data analysis technique used is balanced test, normality test, homogeneity test, and hypothesis test. The results of the study are as follows. First, there are differences in learning outcomes between learning models of Problem Based Learning in conventional Group Investigation and Learning. Second, there are differences in learning activeness between learning models of Problem Based Learning in conventional Group Investigation and Learning. Third, the effectiveness of the learning model of Problem Based Learning in Group Investigation is higher than conventional Learning in improving learning outcomes.Keywords: Problem Based Learning, Group Investigation, Conventional Learning, Learning Outcomes, Activity